Functional outcome of minimally invasive plate osteosynthesis with the use of locking plate in fracture distal end of tibia - Kamble, Prashant; Marathe, Nandan; Sharan, Sudhir; Sharma, Ayush; Sathe, Ashwin; Jogani, Abhinav (International Journal of Research in Orthopaedics, 2020)
Background : Distal tibia fractures or pilon fractures are usually the result of combined compressive and shearing forces, which may lead to instability of the metaphysis. Poor vascularity, lack of muscle cover and frequent intra-articular extension often make these fractures very challenging to manage. There are plenty of options available to treat a distal tibia fracture which includes intramedullary nailing, external fixation, open reduction and internal fixation and minimally invasive plate osteosynthesis (MIPO). The aim of this study was to evaluate the results of MIPO with respect to the healing of fracture site, the incidences of complications and to conclude whether MIPO circumvents the problems of formal open reduction and fixation with other implants. Methods: A series of forty patients with fracture of the distal tibia on preoperative X-rays were treated with minimally invasive plate osteosynthesis using pre-contoured locking plates from June 2014 to October 2018 and followed up at regular intervals with X-rays and monitoring for complications. Result: The functional scores were evaluated using Teeny and Wiss clinical rating system for ankle joints. Thirty-two patients had an ‘Excellent’ or ‘Good’ outcome. One patient was diagnosed with a soft tissue complication and delayed union and 3 patients were diagnosed with malunion without significant functional disability at follow up. Conclusion: Minimally invasive plate osteosynthesis with pre-contoured locking plates is associated with high union rate and good functional outcomes. It is an effective treatment modality for distal tibia fractures.